Novel drug for COVID-19: Virafin a therapeutic breakthrough - Robinson, J; Banerjee, I; Roy, B; Leclézio, A (Journal of Biomedical Sciences, 2021)
Background: Pegylated Interferon Alpha-2b is synthesized via the use of PEG (polyethylene glycol). It is formulated via attaching a 12kDa mono methoxy polyethylene glycol moiety to the recombinant human Interferon Alpha-2b protein. Pegylated Interferon Alpha-2b acts via binding to the (JAK/STAT) Janus kinase signal transducer and activator of the transcription interferon receptor. The Pegylated Interferon Alpha-2b /Virafin binds to the (IFNAR1/2) alpha interferon receptor 1 and 2. Pegylated Interferon Alpha-2b better known as Virafin has been approved by the Drugs Controller General of India. This therapeutic agent is currently under a multicentric phase 3 trial with very promising results being reported. A single subcutaneous dose of Virafin has been shown to decrease the need for oxygen therapy in patients. This reduction in the need for oxygen therapy is a vital factor needed to provide relief to the Indian medical system in light of the recent oxygen shortages faced due to India’s worst wave of COVID-19 cases since the onset of the global pandemic. Pegylated Interferon Alpha-2b/ Virafin confers enhanced viral clearance and bolsters the immune response to induce a quicker recovery in patients with mild to moderate symptoms. Conclusion: It is of paramount importance that further research on Virafin is undertaken as it can hinder the progression of COVID-19, reduce pressure on the inundated health systems, and save countless lives.